Randomized, clinical trial of RT001: Early signals of efficacy in Friedreich's ataxia. Issue 6 (6th April 2018) - Zesiewicz, Theresa; Heerinckx, Frederic; De Jager, Robert; Omidvar, Omid; Kilpatrick, Marcus; Shaw, Jessica; Shchepinov, Mikhail S.
ABSTRACT: Background: RT001 is a deuterated ethyl linoleate that inhibits lipid peroxidation and is hypothesized to reduce cellular damage and recover mitochondrial function in degenerative diseases such as Friedreich's ataxia. Objective: To evaluate the safety, pharmacokinetics, and preliminary efficacy of RT001 in Friedreich's ataxia patients. Design/Methods: We conducted a phase I/II double‐blind, comparator‐controlled trial with 2 doses of RT001 in Friedreich's ataxia patients (9 subjects each cohort). Subjects were randomized 2:1 to receive either RT001 (1.8 or 9.0 g/day), or a matching dose of nondeuterated ethyl linoleate as comparator for 28 days. The primary endpoints were safety, tolerability, and pharmacokinetic analysis. Secondary endpoints included cardiopulmonary exercise testing and timed 25‐foot walk. Results: Nineteen patients enrolled in the trial, and 18 completed all safety and efficacy measurements. RT001 was found to be safe and tolerable, with plasma levels approaching saturation by 28 days. One subject with a low body mass index experienced steatorrhea taking a high dose and discontinued the study. Deuterated arachidonic acid (a brain‐penetrant metabolite of RT001) was found to be present in plasma on day 28. There was an improvement in peak workload in the drug group compared to placebo (0.16 watts/kg; P = 0.008), as well as an improvement trend in peak oxygen consumption (change of 0.16 L/min; P = 0.116), and in stride speed ( P = 0.15). Conclusions: RT001 was found to be safe and tolerable over 28 days, and improved peak workload. Further research into the effect of RT001 in Friedreich's ataxia is warranted. © 2018 International Parkinson and Movement Disorder Society